The Compatibility of Trade Students' Personality and Their Respective Training Environment: An Application of Holland's Theory - Abdullah, Haslee Sharil Lim (1992)
The research was stimulated by a phenomenon among the trade students whose 'output' had not been commensurating with the high 'input' on them. An important influencing factor was the selection system. The research study was carried out in three vocational schools in Negeri Sembilan to study the compatibility of the trade students' personality and their respective trade training environment. Compatibility had been treated as the indicator for the effectiveness of the selection system. A total of 248 Form 5 students from seven trade courses were involved in this study. The data were collected using a questionnaire with the Vocational Preference Inventory (VPI) as its main component. The VPI provided the personality scores of the subjects. Whereas The Occupational Classification provided the environmental code for the occupation most representative of the trade. Statistical tools employed in analyzing the data were the t-test, Kendall's Coefficient of Concordance and Chi-square. The findings of the research study were: (1) realistic personality type was well differentiated with the other personality types except the enterprising p ersonality type; (2) enterprising personality type was the most dominant personality type among the students followed by realistic personality type; (3) the students were incompatible with their trade where their overall mean Compatibility Index was 3.80; (4) there was no significant difference in compatibility between the SRP passers and the SRP failures.